2017
DOI: 10.1515/jpem-2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical and genetic features with nonclassical 21-hydroxylase deficiency and final height

Abstract: The final height of the patients who were treated during childhood was found to be shorter than the final height of patients during the adolescent period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 21 publications
4
26
3
2
Order By: Relevance
“…A recent study from Portugal in which 60% of the patients were NC reported similar results 31 . Within the NC group, the frequency of p.V282L was similar to the frequencies observed in other countries ranging from 45% to 69.5% 17,18,31‐36 …”
Section: Discussionsupporting
confidence: 91%
“…A recent study from Portugal in which 60% of the patients were NC reported similar results 31 . Within the NC group, the frequency of p.V282L was similar to the frequencies observed in other countries ranging from 45% to 69.5% 17,18,31‐36 …”
Section: Discussionsupporting
confidence: 91%
“…While it is well known that poor height prognosis in classical congenital hyperplasia patients could be significantly improved by the early start of appropriate glucocorticoid and mineralocorticoid replacement therapy, the same could not be fully confirmed for NCCAH patients [25]. Most of the studies about this topic in NCCAH, in fact, often showed unclear and discordant results [6-8, 12, 13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It emerged that the genotype could influence phenotype not only in classical form [27], but also in NCCAH, and that some kind of mutation could be responsible of a more severe or mild form of the disease [1, 8, 9, 23]. The data indicated that, NCCAH children with mild/severe genotype exhibited more accelerated growth, BA, and earlier puberty than those with mild/mild genotype, but their AH resulted lower.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonuç olarak, non-klasik KAH hastası kızlar erken ergenlik, kıllanma artışı veya âdet düzensizliği bulgularıyla başvurabilirken erkeklerde belirgin bulgu olmadığından tanı gözden kaçabilir. Bu nedenle literatürde non-klasik KAH tanılı erkeklerin sayısı önemli ölçüde düşüktür (13,14) . Hastalığın OR geçiş göstermesi nedeniyle beklenen eşit cinsiyet dağılımına rağmen, çalışmamızda tüm non-klasik hastalarımızın kız cinsiyetli olması bu duruma bağlanabilir.…”
Section: Gereç Ve Yöntemunclassified